Different Gut Microbial Profiles in African and South Asian Women of Childbearing Age in the Women First (WF) Trial (FS07-05-19). (13th June 2019) - Tang, Minghua; Frank, Daniel; Hendricks, Audrey; Lokangaka, Adrien; Dhaded, Sangappa; Kemp, Jennifer; Ir, Diana; Hambidge, Michael; Krebs, Nancy
Abstract: Objectives: To characterize and compare the gut microbial structures in women of childbearing age from Africa (the Democratic Republic of the Congo, DRC) and South Asia (India) Methods: Women of childbearing age were recruited from rural DRC and India as part of the WF preconception maternal nutrition trial. Findings presented include the gut microbiota (16S rRNA sequencing) of women at the time of randomization prior to conception in the WF trial and represented participants from two of the WF sites, with distinctive ethnicity, diet, culture and geographical locations. Women were recruited from 12 villages in rural DRC and 9 villages from rural India. 24-h dietary recalls were conducted on half of the participants during the first trimester of pregnancy. Results: Stool samples were collected from n  = 217 women (DRC n  = 117; India n  = 100). Alpha diversity of the gut microbiota was higher in DRC than in India using Chao1 (91 ± 11 vs. 82 ± 12, P  < 0.001). At Phylum level, the three most abundant phyla were Bacteroidetes (51%), Firmicutes (33%) and Proteobacteria (7%) with no difference between sites. At Genus level, Prevotella remained the only strain that was over 10% abundance (DRC: 27 ± 11%; India: 29 ± 13%; P  = 0.32). Some fiber fermenting strains Succinivibrio (DRC: 3.2 ± 0.8%; India: 3.2 ± 0.6%; P  = 0.11) and Roseburia (DRC: 2.0 ± 0.3%; India: 2.1 ± 0.4%; P  = 0.31) remained at relatively high abundance without differences between sites. Bifidobacterium was higher in India (4.95 ± 1.0%) than DRC (0.3 ± 0.1%; P  = 1.4E-28), and so was Lactobacillus (DRC: 0.2 ± 0.0%; India: 1.2 ± 0.1%; P  = 3.0E-14) and Faeclibacterium (DRC: 6.0 ± 1.7%; India: 8.4 ± 2.9%; P  = 2E-7). Ruminococcus was higher in DRC (2.3 ± 0.7%) than in India (1.8 ± 0.4%; P  = 1.3E-5). These observations were consistent with dietary intakes of high plant-based foods for both countries; India being primarily vegetarian with regular fermented dairy consumption and DRC consumes animal-based foods regularly. The gut microbiota was not affected by any demographical variables. Conclusions: Consumption of plant-based foods, animal-flesh foods and fermented dairy foods all had independent effects on the gut microbiota, and the effects of diet apparently overrides other potential factors such as socioeconomic status. Funding Sources: Bill & Melinda Gates Foundation; NIH, NICHD & ODS.